The Relationship Between Perceived Family Support and Career Decidedness among Vocational School of Health Services Students - Muammer Salim; Faruk Yaşar Gürdal (SDÜ SAĞLIK BİLİMLERİ DERGİSİ, 2026)
Objective: This study examined the relationship between perceived family support and career decidedness among associate degree students enrolled in a Vocational School of Health Services and tested the extent to which perceived family support predicts career decidedness. It also investigated whether career decidedness differs by gender, age group, grade level, program, parental education, and perceived socioeconomic status. Methods: Using a quantitative correlational design, the study included 531 students from a state university’s Vocational School of Health Services. Data were collected via a Personal Information Form, the Perceived Family Support Scale (20 items), and the Career Decidedness Scale (6 items). Analyses were conducted in SPSS 23.0 using descriptive statistics, Pearson correlation, simple linear regression, independent samples t-test, and one-way ANOVA. Results: Perceived family support was positively and significantly associated with career decidedness (r=0.147,p0.05). Conclusion: One of the main findings of the study is that perceived family support makes a positive yet limited contribution to helping students clarify their career decisions. In addition, differences by class level indicate that career decidedness may weaken as the educational process progresses. This finding suggests that students approaching graduation may experience uncertainty about their professional future and underscores the importance of supportive career guidance practices aimed at sustaining decision clarity in the later stages of education.